2022
DOI: 10.1177/03400352211066941
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the use of agricultural information by Vietnamese farmers

Abstract: This study examined the factors affecting the use of agricultural information by Vietnamese cereal farmers. A sample size of 245 cereal farmers was selected and surveyed. The participants were classified into small, medium and large cereal farmers. Descriptive statistics and inferential statistics were applied to analyse the data. The results show that large farmers used information from preferred traders, extension workers, input suppliers, mobile phones and the Internet; smaller farmers employed information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Mtega's study recommended that radio stations should increase the number of agricultural programmes to be aired per week, while the government would reduce tariffs associated with the acquisition and maintenance of radio services. This is also adjoined by several other studies (such as Svensson, and Yanagizawa, 2009;Musawi;Kaske, 2020;Hoang et al,2022) that where modern information sources such as radio, television, mobile free short messaging services, social media, farmer's field visit, workshops and training are strategically deployed as they would offer enormous gain for agricultural information transfer.…”
Section: Horticultural Farming Information Sources and Their Accessib...mentioning
confidence: 89%
See 2 more Smart Citations
“…Mtega's study recommended that radio stations should increase the number of agricultural programmes to be aired per week, while the government would reduce tariffs associated with the acquisition and maintenance of radio services. This is also adjoined by several other studies (such as Svensson, and Yanagizawa, 2009;Musawi;Kaske, 2020;Hoang et al,2022) that where modern information sources such as radio, television, mobile free short messaging services, social media, farmer's field visit, workshops and training are strategically deployed as they would offer enormous gain for agricultural information transfer.…”
Section: Horticultural Farming Information Sources and Their Accessib...mentioning
confidence: 89%
“…Studies (e.g. Salau et al, 2013;Ndimbwa et al, 2019Abebe et al, 2019Ng'atigwa et al, 2020;Hoang et al, 2022) considers use of modern channels such as mobile phones or the Internet to access agricultural information as an important milestone for enhancing agricultural information access by farmers. Unless farmers have information at their fingertips, they will also lose out on market opportunities for their produce.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Meena [16] noted that the access level was low among the farmers while some of the farmers were also reported to get less amount of credit. Hoang et al [7] conducted a study and reported that access to credit has the potential to increase the financial ability of smallholder farmers to use ICT tools in agriculture. Although a few who accessed the credit got a small amount.…”
Section: Access Level To Agricultural Creditmentioning
confidence: 99%
“…Most of the farmers practice farming on a piece of land of fewer than 3 acres [6]. The farmers can easily adopt the novel techniques when they receive the information timely through constructive extension dissemination techniques like ICT tools [7]. The tools refer to a set of technological devices and resources used to receive, store and communicate information.…”
Section: Introductionmentioning
confidence: 99%